A spatially supported forced-choice recognition test reveals children’s long-term memory for newly learned word forms - Gordon, Katherine R.; McGregor, Karla K. (Frontiers in Psychology, 2014)
Children’s memories for the link between a newly trained word and its referent have been the focus of extensive past research. However, memory for the word form itself is rarely assessed among preschool-age children. When it is, children are typically asked to verbally recall the forms, and they generally perform at floor on such tests. To better measure children’s memory for word forms, we aimed to design a more sensitive test that required recognition rather than recall, provided spatial cues to off-set the phonological memory demands of the test, and allowed pointing rather than verbal responses. We taught 12 novel word-referent pairs via ostensive naming to sixteen 4-to-6-year-olds and measured their memory for the word forms after a week-long retention interval using the new spatially-supported form recognition test. We also measured their memory for the word-referent links and the generalization of the links to untrained referents with commonly used recognition tests. Children demonstrated memory for word forms at above chance levels; however, their memory for forms was poorer than their memory for trained or generalized word-referent links. When in error, children were no more likely to select a foil that was a close neighbor to the target form than a maximally different foil. Additionally, they more often selected correct forms that were among the first six than the last six to be trained. Overall, these findings suggest that children are able to remember word forms after a limited number of ostensive exposures and a long-term delay. However, word forms remain more difficult to learn than word-referent links and there is an upper limit on the number of forms that can be learned within a given period of time.